Electric Motor Speed Control on Trimaran Ships Based on Sliding Mode Control - Ni Kadek Sri Prameswari; Edi Kurniawan; Diyah Purwitasari (RING ME, 2025)
Ships are a means of transportation used in maritime transport activities, yet maintaining propulsion stability and efficiency remains a critical challenge, especially for multi hull vessels such as trimarans operating under dynamic sea conditions. Conventional controllers such as PID and field oriented control (FOC) often struggle to adapt to fluctuating loads and external disturbances. This study addresses that gap by applying Sliding Mode Control (SMC) for brushless DC (BLDC) motor speed regulation on a trimaran prototype. The system employs an STM32 microcontroller integrated with voltage, current, and RPM sensors to provide real time monitoring and robust control. Both static and dynamic tests were conducted at various speed setpoints with artificial wave disturbances. The results indicate that the SMC based system effectively reduced RPM deviation from ±550 RPM in uncontrolled systems to as low as ±3–15 RPM, while current and voltage consumption remained stable within 5%. Furthermore, propulsion efficiency improved by approximately 17% compared to conventional PID control. The most stable performance was achieved at the 8000 RPM setpoint, where current consumption reached 3.9–4.1 A, lower than the 4.7 A observed in uncontrolled operation. However, system performance declined at 10,000 RPM due to nonlinear load effects. These findings demonstrate that SMC provides a robust, adaptive, and energy efficient solution for BLDC motor control in trimaran propulsion, offering significant advantages over traditional methods and serving as a foundation for further optimization in high speed applications.